Fostering The Use Of Indigenous Knowledge System To Teach Freehand Sketches In Engineering Graphics and Design - Princess Blose; Thokozani Isaac Mtshali (Faculty of Engineering, Universitas Negeri Yogyakarta, 2025)
Teacher's expertise in design plays an important role in communicating drawing messages. This expertise is often influenced by their general knowledge and culture's identity and core principles, which is all part of Indigenous Knowledge. The purpose of this study was to explore teachers experiences in the use of Indigenous Knowledge System (IKS) to teach freehand sketches in engineering graphics and design. This study used a qualitative research approach and phenomenological design to understand participants experiences. Indigenous knowledge framework was employed to capture all relevant information. Interviews and classroom observations were used to collect data and thematic analysis was used to analyse it. So, this study discovered that teachers used drawing designs inspired by South African cultural designs taken from Indigenous Ndebele decoration patterns, and Contextualised storytelling to foster Indigenous Knowledge when teaching freehand sketches in engineering graphics and design. As a recommendation, this study is still calling for a content knowledge structure that revolves around the application of IKS, rather than focusing just on a small number of topics where teachers must find creative ways to incorporate IKS.